2018
DOI: 10.1093/cvr/cvy105
|View full text |Cite
|
Sign up to set email alerts
|

β2-adrenergic receptor autoantibodies alleviated myocardial damage induced by β1-adrenergic receptor autoantibodies in heart failure

Abstract: β2-AAs were capable of antagonizing the effects imposed by β1-AAs both in vitro and in vivo. The imbalance of β1-AAs and β2-AAs in patients with HF is a mechanism underlying HF progression, and the increasing ratio of β1-AAs/β2-AAs should be considered a clinical assessment factor for the deterioration of cardiac function in patients with HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Assessment of the effect of human aabs on downstream signalling might be even further complicated by the co‐existence of aabs against different target proteins, which could then enhance (additive effect) or inhibit (opposing effect) downstream signalling and would require a panel of different epitope‐mimicking CPs to be therapeutically used on a case‐to‐case basis (e.g. human anti‐β 1 ‐aabs were shown to increase cAMP production, whereas human anti‐M2‐aabs inhibit cAMP production, 46 or myocardial damage induced by anti‐β 1 ‐aabs in heart failure was found to be alleviated by human anti‐β 2 ‐aabs 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of the effect of human aabs on downstream signalling might be even further complicated by the co‐existence of aabs against different target proteins, which could then enhance (additive effect) or inhibit (opposing effect) downstream signalling and would require a panel of different epitope‐mimicking CPs to be therapeutically used on a case‐to‐case basis (e.g. human anti‐β 1 ‐aabs were shown to increase cAMP production, whereas human anti‐M2‐aabs inhibit cAMP production, 46 or myocardial damage induced by anti‐β 1 ‐aabs in heart failure was found to be alleviated by human anti‐β 2 ‐aabs 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…The selectivity and toxicity of DOX to heart have clearly been demonstrated in both in vivo and in vitro studies. [12][13][14] Through this study, we excavated the functional contribution and molecular mechanisms of IGF-IIRα in DOXinduced cardiotoxicity. Our results showed that organ specific IGF-IIRα overexpression in the heart leads to cardiac structural and functional anomalies which were aggravated by DOX treatment causing more severe cardiac functional impairment and enhanced cardiac injury that may gradually progress to heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that β 1 -AR and β 2 -AR could form heterodimers, although they also found that the autoantibody β 1 -AA did not bind to β 2 -AR [ 15 ]. We found that β 1 -AA could inhibit heterodimerization of β 1 / β 2 -AR, observing laboratory experiments on animals at Capital Medical University.…”
Section: Discussionmentioning
confidence: 99%
“…Fresh medium was added and transferred to a 6-well plate for cell culture and 2 ml of DMEM low-glucose medium was added to each well. Detection of the beating frequency of NRCMs [ 15 ] was as follows: the culture medium was replaced on the day of the experiment and stably incubating in a 37° C cell culture incubator for 30 minutes, the 6-well plate was placed on a constant-temperature table of inverted microscopy, and a total of 10 fields of view of 3 six-well plates were randomly observed. Each field was measured for 30 seconds at a time, and the number of synchronized contractions of an isolated single cell or a group of cardiomyocytes in the untreated group was measured.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation